2015
DOI: 10.1017/s0007485315000292
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota associated with pollen, bee bread, larvae and adults of solitary beeOsmia cornuta(Hymenoptera: Megachilidae)

Abstract: Using cultivation-dependant method, we isolated 184 strains from fresh and old bee bread, pollen, larvae and adults of solitary bee Osmia cornuta. The 16S rDNA sequencing of 79 selected isolates gave the final species-specific identification of strains. Phylogenetic analysis indicated that microbiota isolated from five different sources were represented with 29 species within three different phyla, Firmicutes with 25 species, Actinobacteria with only one species and Proteobacteria with three species of Enterob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 32 publications
4
47
0
Order By: Relevance
“…On the other hand, solitary bee nests harbor highly diverse bacterial communities (Keller, Grimmer, & Steffan‐Dewenter, ; Lozo et al, ; McFrederick & Rehan, ; Mohr & Tebbe, ; Voulgari‐Kokota, Grimmer, Steffan‐Dewenter, & Keller, ). However, only few studies have dealt with their role in larval health (Keller et al, ; McFrederick, Vuong, & Rothman, ) or their acquisition routes (McFrederick et al, ; Voulgari‐Kokota, McFrederick, Steffan‐Dewenter, & Keller, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, solitary bee nests harbor highly diverse bacterial communities (Keller, Grimmer, & Steffan‐Dewenter, ; Lozo et al, ; McFrederick & Rehan, ; Mohr & Tebbe, ; Voulgari‐Kokota, Grimmer, Steffan‐Dewenter, & Keller, ). However, only few studies have dealt with their role in larval health (Keller et al, ; McFrederick, Vuong, & Rothman, ) or their acquisition routes (McFrederick et al, ; Voulgari‐Kokota, McFrederick, Steffan‐Dewenter, & Keller, ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the multiple aspects of solitary bee ecology can form distinctive nesting conditions for different species, we test the hypothesis that different pollen foraging patterns could establish different routes for bacterial colonization in the nest. Previous studies have undertaken the task of characterizing solitary bee nest microbiota (Keller et al, ; Lozo et al, ; McFrederick et al, ; Voulgari‐Kokota, Grimmer, et al, ) or have identified the plant composition of pollen provisions (Danner, Keller, Härtel, & Steffan‐ Dewenter, ; Sickel et al, ; Villanueva‐Gutiérrez & Roubik, ). Simultaneous examination of pollen composition and pollen microbiota from the nests of a wild bee species has shown covariation across different landscapes, even though the causality of this association was not clear (McFrederick & Rehan, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, McFrederick et al [9] found that flower and wild megachilid bee samples can share the same taxon of Lactobacillus, and that this bacterium can dominate the microbial community of all life stages of the bee and its pollen provision. Likewise, in 2015, Lozo et al [14] found that pollen collected by the mason bee Osmia cornuta contains mostly the environmentally acquired cosmopolitan bacterium Pantoea agglomerans. Recently, it has been established that providing honey bees with different sources of floral forage can subtly alter the gut microbiome [15,16], and that bees may alter the composition of floral microbial diversity [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Pantoea agglomerans strains occur commonly -usually as symbionts -in arthropods, mostly insects [68]. Among others, they were found to be associated with social insects, such as bees [69,70], ants [71], and termites [72]. N 2 -fixing P. agglomerans strains found in the guts of wood-eating termites were identified as a potential source of nitrogen for these insects [72].…”
Section: Causative Agent Of Infections In Animalsmentioning
confidence: 99%